2015
DOI: 10.1016/j.neuroscience.2015.06.054
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of lixisenatide and liraglutide in the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine mouse model of Parkinson’s disease

Abstract: Glucagon-like peptide 1 (GLP-1) is a growth factor. GLP-1 mimetics are on the market as treatments for type 2 diabetes and are well tolerated. These drugs have shown neuroprotective properties in animal models of neurodegenerative disorders. In addition, the GLP-1 mimetic exendin-4 has shown protective effects in animal models of Parkinson's disease (PD), and a clinical trial in PD patients showed promising first results. Liraglutide and lixisenatide are two newer GLP-1 mimetics which have a longer biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
120
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(122 citation statements)
references
References 35 publications
2
120
0
Order By: Relevance
“…Motor coordination and activity was improved by the newer GLP-1 mimetics, and the expression of TH was also rescued by both drugs. Importantly, levels of the pro-apoptotic signal BAX were reduced, the cell survival signal Bcl-2 was increased by both drugs (Liu et al, 2015a). Similar protective effects were observed with the GLP-1 analogue (Val8)GLP-1-Glu-PAL (Zhang et al, 2015).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Motor coordination and activity was improved by the newer GLP-1 mimetics, and the expression of TH was also rescued by both drugs. Importantly, levels of the pro-apoptotic signal BAX were reduced, the cell survival signal Bcl-2 was increased by both drugs (Liu et al, 2015a). Similar protective effects were observed with the GLP-1 analogue (Val8)GLP-1-Glu-PAL (Zhang et al, 2015).…”
Section: Discussionmentioning
confidence: 66%
“…Mimetics of GLP-1 and GIP have shown neuroprotective effects in animal models of Alzheimer's disease (Bomfim et al, 2012;Duffy and Holscher, 2013;Faivre and Holscher, 2013a, b;Li et al, 2010;McClean et al, 2011) and were found to re-sensitise insulin signaling in the brain (Long-Smith et al, 2013). GLP-1 receptor agonists also have neuroprotective effects in animal models of PD (Bertilsson et al, 2008;Harkavyi et al, 2008;Li et al, 2009;Liu et al, 2015a;Zhang et al, 2015). The GLP-1 mimetic exendin-4 showed protective effects in a pilot clinical study in PD patients (Aviles-Olmos et al, 2013a;Aviles-Olmos et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown in a previous study that Val(8)GLP--1(glu--PAL) is neuroprotective and protects memory and synaptic plasticity in diabetic animals (Lennox et al, 2013). We also have previously shown that liragutide and the newer diabetes drug lixisenatide are protective in the MPTP mouse model of PD (Liu et al, 2015). Here, we demonstrate for the first time that Val(8)GLP--1(glu--PAL) is also neuroprotective in this mouse model of PD.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, there has been evidence that GIP enhances cell survival in both β-cells of the pancreas and in neurons [53]. Glucagonlike peptide-1 (GLP-1) is also an incretin hormone and analogues such as Lixisenatide, Liraglutide and Exenatide have shown neuroprotective effects in animals and humans [54][55][56][57]. Li et al provided evidence for the role of GIP in neuronal survival in animal models of PD [58].…”
Section: The Role Of Gip Glp-1 and Dpp4mentioning
confidence: 99%